2020
DOI: 10.1007/s42452-020-2065-0
|View full text |Cite
|
Sign up to set email alerts
|

Lead removal efficiency of various natural adsorbents (Moringa oleifera, Prosopis juliflora, peanut shell) from textile wastewater

Abstract: The present study deals with the class of natural adsorbents such as Moringa oleifera, Prosopis juliflora seeds and peanut shell for the removal of heavy metal (lead: Pb) from textile wastewater. The above adsorbents were characterized by Fourier transform infrared and scanning electron microscope to predict the functional groups and surface morphology. The effect of adsorbent dose, contact time, metal concentrations and pH on lead removal was studied in batch experiment and found that the maximum removal of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“… Reddy et al ( 2010b ) MOB 30.4 Langmuir The kinetic studies revealed that the biosorption process followed the pseudo-second-order kinetic model. Reddy et al ( 2011 ) MOS 29.6 Langmuir No indication of the mechanism in this work Marques et al ( 2012 ) MOS 412.3 Langmuir Physisorption nature Çelekli et al ( 2019 ) MOH 14.7 Langmuir/sips Physisorption nature (ΔH° < 40 kJ/mol) de Bezerra et al ( 2020 ) MOS 23.1 - No indication of the mechanism in this work but confirm the surface heterogeneity Araújo et al ( 2010a ) MOF 5.6 Langmuir No indication of the mechanism in this work Gautam et al ( 2020a ) MOB 25.2 Langmuir No indication of the mechanism in this work Mnisi and Ndibewu ( 2017 ) MOP and MOH 9.6 Langmuir No indication of the mechanism in this work Adebayo et al ( 2019 ) MOS 238 Langmuir SEM-EDX analysis confirmed an exchange of Mg(II) and K(I) for Cu(II) on MOS and the binding energy for the ion exchange mechanism is 8 to 9 kJ mol −1 Acheampong et al ( 2011 ) SMOS 90.3 % for 25 mg/L of methylene blue - At a pH value of 6.5, the carboxylic groups are deprotonated and are negatively charged. These negatively charged carboxylate ligands are likely to attract the cationic dye species.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“… Reddy et al ( 2010b ) MOB 30.4 Langmuir The kinetic studies revealed that the biosorption process followed the pseudo-second-order kinetic model. Reddy et al ( 2011 ) MOS 29.6 Langmuir No indication of the mechanism in this work Marques et al ( 2012 ) MOS 412.3 Langmuir Physisorption nature Çelekli et al ( 2019 ) MOH 14.7 Langmuir/sips Physisorption nature (ΔH° < 40 kJ/mol) de Bezerra et al ( 2020 ) MOS 23.1 - No indication of the mechanism in this work but confirm the surface heterogeneity Araújo et al ( 2010a ) MOF 5.6 Langmuir No indication of the mechanism in this work Gautam et al ( 2020a ) MOB 25.2 Langmuir No indication of the mechanism in this work Mnisi and Ndibewu ( 2017 ) MOP and MOH 9.6 Langmuir No indication of the mechanism in this work Adebayo et al ( 2019 ) MOS 238 Langmuir SEM-EDX analysis confirmed an exchange of Mg(II) and K(I) for Cu(II) on MOS and the binding energy for the ion exchange mechanism is 8 to 9 kJ mol −1 Acheampong et al ( 2011 ) SMOS 90.3 % for 25 mg/L of methylene blue - At a pH value of 6.5, the carboxylic groups are deprotonated and are negatively charged. These negatively charged carboxylate ligands are likely to attract the cationic dye species.…”
Section: Introductionmentioning
confidence: 57%
“…Knowing that the Moringa is a miraculous tree native to the foothills of the Himalayas (northern India, Pakistan, Bangladesh, and Nepal) and Africa (Anwar et al 2007 ; Paliwal et al 2011). The perspective sorption properties of all parts (seeds, leaves, barks, and husk) of this plant have been proposed by multiple research groups for the sequestration of the notable hazardous and toxic heavy metal ions (e.g., Cu(II), Ni(II), Pb(II), Cd(II), Hg(II)) in wastewater (Reddy et al 2010a , b , 2012 ; Kebede et al 2018 ; Çelekli et al 2019 ; de Oliveira et al 2019 ; de Bezerra et al 2020 ; Gautam et al 2020a ). The metal ions have been declared as prioritized pollutants by many countries (Arora and Chauhan 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking advantage of available biomass sources, many studies have used them as green adsorbents for the removal of lead. Indeed, Gautam et al (2020) reported the good outcomes of lead adsorption with capacity (1.4-5.6 mg/g) and efficiency (72-86%) at pH 6.0 using the above biosorbents. However, their adsorption performance was generally low, and the reusable property was not reported yet.…”
Section: Leadmentioning
confidence: 97%
“…The dead leaves of tall fescue which contribute 12.6%–16% of the total shoot biomass significantly removed 73.4%–87.2% of total Cd in wastewater. Biosorbent through macrophytes species, such as Phragmites australis (Bianchi et al, 2021; Southichak et al, 2006), Juncus effuses (Ladislas et al, 2015), Carex riparia (Ladislas et al, 2015), Melocanna baccifera (Lalhruaitluanga et al, 2010), and Moringa oleifera (Gautam et al, 2020) were also studied and reported by scientific community. Bianchi et al (2021) investigated the role of reed biomass as a biosorbent material for the removal of Fe, Cu, and Zn from industrial wastewater.…”
Section: Classification Of Cwsmentioning
confidence: 99%